Pengaruh knowledge management dan transformational leadership terhadap employee performance melalui job satisfaction sebagai variabel intervening - Evika, Wafiq Annisa; Budiono (Universitas Negeri Surabaya, 2024)
The aim of this research is to examine and analyze the influence of knowledge management and transformational leadership on employee performance through job satisfaction at one of the marble companies in Surabaya. This research is causality research with a quantitative approach. The sampling technique used a saturated sample with a total of 68 respondents. The statistical analysis used in this research is partial least squares (PLS) with the help of SmartPLS 4.0 software. The results of this research prove that knowledge management has a positive and significant effect on employee performance. Transformational leadership has a positive and significant effect on employee performance. Knowledge management has a positive and significant effect on job satisfaction. Transformational leadership has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction is able to mediate the influence between knowledge management and transformational leadership on employee performance.